The Effect of Transformational Leadership of School Principals on the Performance of ICT Teachers in the Implementation of Learning at SMAN XYZ - Nikita Anisa; Rini Werdiningsih; Emiliana Sri Pudjiarti (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effect of school principals' transformational leadership on the performance of ICT teachers in implementing digital learning at SMAN XYZ, specifically examining how four dimensions of transformational leadership Influence teacher motivation, creativity, and innovation in technology integration. This quantitative research employed an explanatory correlational design with 20 ICT teachers as respondents selected through purposive sampling. Data were collected using validated questionnaires adapted from the Multifactor Leadership Questionnaire (MLQ) by Bass and Avolio (1994) for transformational leadership and the TPACK framework by Koehler and Mishra (2009) for teacher performance. Simple linear regression analysis was conducted using SPSS 25 to test the research hypothesis. Results demonstrate that transformational leadership significantly and positively influences ICT teacher performance (β = 0.672, p = 0.003 < 0.05), explaining 67.2% of performance variance. The principal's transformational leadership scored highly (4.3/5), with individualized consideration contributing most significantly to teacher performance. ICT teacher performance reached a high category (4.1/5), with the most substantial achievement in technology-based lesson planning, although challenges remain in independent digital content development and innovative assessment methods. Theoretically, this research strengthens transformational leadership Theory in digital Education contexts and supports the TPACK framework's emphasis on leadership support for technology integration. Practically, findings guide principals to optimize transformational leadership through enhanced mentoring, professional development programs, and the creation of an innovation culture. The study offers an empirical foundation for educational policymakers to develop school leadership training programs focused on digital transformation, while highlighting the importance of individualized consideration in supporting teacher technology competency development.